Competitiveness Dynamics of the New Energy Vehicle Innovation Ecosystem: A Functional–Structural Analysis under New-Generation Productive Forces - Sun, Baole (Asia Pacific Economic and Management Review, 2026)
In the context of a global shift toward green, intelligent, and high-end development, this study examines how New-Generation Productive Forces (NGPF) drive the competitiveness of the New Energy Vehicle (NEV) industrial innovation ecosystem. We develop a comprehensive evaluation framework integrating functional (innovation inputs, outputs, and performance) and structural (collaboration network characteristics) dimensions. Using a hierarchical entropy weighting method and TOPSIS, we measure the competitiveness of Xi’an’s NEV innovation ecosystem from 2016 to 2023 and analyze its evolution across distinct phases. The results show that overall competitiveness steadily increased, with notable acceleration after 2020. In early stages, improvements were driven primarily by innovation inputs and outputs, whereas in later stages the strengthening of network structure (increasing density, clustering, and core stability) played an increasingly critical role. Functional performance and network structure demonstrated a complementary, co-evolving relationship: continuous innovation investment built the foundation for competitiveness, while an optimized collaboration network amplified and sustained those gains. The findings highlight the enabling role of NGPF—through technological breakthroughs, factor reconfiguration, and network synergy—in transforming the NEV ecosystem from being factor-driven to system-driven. This study contributes a dual-dimensional evaluation approach for industrial innovation ecosystems and provides empirical insights for policymakers to enhance both the “hard” innovation capacity and the “soft” collaborative linkages in strategic emerging industries.